HAM dan Hukum Islam : (Tinjauan Atas Penerapan Hukum Di Masyarakat) - Gasim Yamani (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2021)
Ham as an agreement made by humans, has legal force that is recognized by the whole world. On the other hand, Islam as a religion also has a source of law that regulates human life and of course the laws regulated in Islam are in the name of God and justice. Human rights debates often occur when Islamic law wants to be applied, for example, cutting hands, capital punishment and so on. Though the punishment is in the name of God and justice. This is the object of a research study on how Islam views human rights, this study has also been carried out by several researchers such as Sitti Aminah's writing with the title